Comparison of the nova stat profile prime plus point of care analyser to the radiometer ABL 800 and Abbott i-stat - Jawa, Ali Azher (My University, 2020)
Background: Point of Care Testing (POCT) plays an integral role in the management of acutely ill patients presenting to the Emergency Department (ED). Due to its rapid turnaround time, POCT has been shown to improve ED workflow, reduce unnecessary admissions and lessen the burden on ED staff. The aim of the study was to compare the accuracy, precision and linearity of the Nova Stat Profile Prime Plus® to the Radiometer ABL800 FLEX® and the Abbott i-stat Chem8+® POCT analyzers.Methods: A convenience sample of 150 discarded whole blood specimens were obtained and analyzed. Paired test measurements were conducted for method comparison. Accuracy was measured by pairing individual results from the Nova Stat Profile Prime Plus® with either the Radiometer ABL 800 FLEX® or the Abbot i-stat Chem8+® analyzers by calculating the differences. Results: The with-in run percentage coefficient of variation (%CV) was below 2.4% for pH, carboxyhemoglobin (COHb), deoxyhemoglobin (HHb), total hemoglobin (tHb), total bilirubin (tBil), sodium (Na), potassium (K), chloride (Cl), ionized calcium (iCa), urea, glucose and lactate, and was below 5.1% for all other analytes. The day-to-day %CV was below 1.6% for pH, COHb, HHb, tHb, tBil, Na, K, Cl, iCa, urea, glucose and lactate, and below 6.10% for all other analytes. The correlation coefficient (r) was 0.351 and ranged from 0.897 to 0.998 for all analytes. The mean bias was minimal for all analytes. Conclusion: There was a good correlation between the Nova Stat Profile Prime Plus® and the Radiometer ABL800 FLEX® / Abbott i-STAT Chem8+® POCT analyzers. The Stat Profile Prime Plus® exhibited good precision both within-run and day-to-day.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Emergency Medicine to the Faculty of Health of the University of the Witwatersrand, Johannesburg, 2020